Analyzing the Influence of Cognitive Distortions on the Formation of Criminal Behavior: A Systematic Review of Theories and Recent Research - Agnes Sandra; Pralayar Fanny Fadesti; Tina Khostarina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The phenomenon of cognitive distortions in criminal behavior is increasingly gaining attention in the fields of forensic psychology and criminology. Cognitive distortions refer to irrational or deviant thought patterns that lead individuals to misinterpret reality in a way that justifies or rationalizes their behavior, including criminal acts. In the context of crime, cognitive distortions often serve as a justification mechanism, enabling offenders to perceive their criminal actions as acceptable or even warranted, despite contradicting societal norms. This study systematically reviews the role of cognitive distortions in criminal behavior, emphasizing the types of distortions, causal relationships, and implications for interventions. A systematic literature review (SLR) method is employed, synthesizing empirical studies and theories on cognitive distortions in offenders. The findings show consistent evidence that cognitive distortions such as self-serving biases and victim-blaming are associated with externalizing behaviors and criminal activity. Additionally, cultural and methodological gaps in the current research are identified, suggesting the need for longitudinal studies and cross-cultural comparisons. This research highlights the importance of early interventions targeting cognitive distortions to prevent criminal behavior, particularly in high-risk groups like adolescents.